Assessment of Sound Loudness Using Self-Assessment Profile of Aided Loudness (PAL) Questionnaire in Young Individuals and Elderlies with Moderate and Severe Hearing Loss Using Hearing Aid - Fatemeh Abdolmajidi; Somayeh Falahzadeh; Alireza Golchin-Namdari; Soraya Kohzadi (Vesnu Publications, 2017)
Introduction: Common audiometric tests can assess if there is any hearing injury or not, but they can not assess the impact of disability due to hearing loss, individual's satisfaction level from rehabilitation services, and the impact of disability on life, due to hearing loss. These items can be assessed using self-assessment questionnaires. This study aimed to use self-assessment Profile of Aided Loudness (PAL) questionnaire to compare satisfaction and loudness levels of sounds in young individuals and elderlies with moderate and severe hearing loss using hearing aid. Materials and Methods: In this cross-sectional study, 20 young individuals with age range of 20 to 40 years and 20 elderlies with age range from 60 to 80 years were enrolled. Satisfaction and sound loudness levels of the hearing aid were assessed using self-assessment PAL questionnaire. Data were collected and analyzed using computer statistical information analysis software. Results: Loudness level had no significant differences among young individuals and elderlies, and women and men. Loudness level had no significant differences for soft sounds, but for average and loud sounds, the differences were significant. Satisfaction levels did not show any significant differences between moderate and severe hearing loss, and between women and men; but the difference between young individuals and elderlies was significant. Conclusion: PAL index is efficient to assess the understood sound loudness in an individual with and without hearing aid. Comparing the outcomes of this questionnaire with normal levels is used to select and adjust the hearing aid. The results of this study show that loudness understanding is affected by the level of hearing loss, and satisfaction level is affected by age factor.